Identifikasi Tumbuhan Berbiji Terbuka (Gymnospermae) di Kawasan Wisata Batu Gajah, Cibiru Wetan, Kecamatan Cileunyi, Kabupaten Bandung, Jawa Barat - Fenita Putri Dekaliyani; Husna Aulia Muthi’ah; Mochammad Ikbal Fatoni; Ateng Supriatna (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Open-seeded plants or gymnosperms are plants with seeds that are not protected by the ovary, so that the seeds can be seen directly without peeling them first from the ovary. This group of gymnosperms can be found in the Batu Kuda tourist area, Cibiru Wetan, Cileunyi District. Therefore, the aim of this research is to determine the diversity of Gymnosperm plants in the Batu Kuda Cibiru Wetan tourist area, Cileunyi District. The method used is direct exploration/observation in the area around the Batu Kuda tourist attraction. The results of observations show that there are five species that occupy the Batu Kuda tourist area, including Pinus merkusii, Pinus yunnanensis, Sequoia sempervirens, Juniperus chinensis, and Juniperus deppeana. The five plants found came from the Pinopsida class.